The discourse analysis of articles introducing restaurants in english and vietnamese - Phạm,Thị Minh Hiền (ĐHĐN., 2014)
This study aimed at conducting a discourse analysis of articles introducing restaurants in English and Vietnamese. Therefore, it analyzed, compared and contrasted the differences and similarities in articles introducing restaurants in English and Vietnamese in terms of layout, grammatical features, lexical features and cohesive devices. The data for analysis in this thesis were 200 samples of articles introducing restaurants from popular and prestigious websites in the United States, the United Kingdom, Australia and Vietnam. The findings showed that articles introducing restaurants in English and Vietnamese have a general layout with four parts: Headline, Body copy, Illustration and Standing details. Lexical features showed words to help create a friendly, attractive setting with delicious foods, promising the customers memorable feelings. Those words are also strongly emotive and serve as encouraging factors to customers. With regard to syntactic features, this thesis deals with the distinctive ones as follows: imperative sentences, simple sentences, ellipsis in declarative sentences and active and passive voice. Besides, five types of cohesive devices including reference, ellipsis, conjunctions, repetition and lexical cohesion make the texts of introducing restaurants highly cohesive. Those devices are manipulated in the way that they target customers directly with the creation of encouraging power and strong impression. Based on the findings, the thesis gives out some implications and suggestions for teaching and learning in both languages. It is hoped that the result of the thesis is a useful reference to those who are interested in the field of restaurants and articles introducing restaurants.